Dynamic instabilities on a charged boundary: influence of mass transfer - Gichan, O.I. (Reports of the National Academy of Sciences of Ukraine, 2016)
The mass transfer functions for electrodes of spherical, cylindrical, and planar forms in a model electrocatalytic process with the potential-dependent adsorption/desorption of electroactive particles and a preceding chemical reaction in the Nernst diffusive layer are calculated. The role of this function in the appearance of dynamic instabilities leading to bistable steady states and periodic oscillations of the current in the non-equilibrium system is determined.